Model systems for regeneration: zebrafish - Marques, Ines J.; Lupi, Eleonora; Mercader, Nadia (Development (Cambridge), 2019)
Tissue damage can resolve completely through healing and regeneration, or can produce permanent scarring and loss of function. The response to tissue damage varies across tissues and between species. Determining the natural mechanisms behind regeneration in model organisms that regenerate well can help us develop strategies for tissue recovery in species with poor regenerative capacity (such as humans). The zebrafish (Danio rerio) is one of the most accessible vertebrate models to study regeneration. In this Primer, we highlight the tools available to study regeneration in the zebrafish, provide an overview of the mechanisms underlying regeneration in this system and discuss future perspectives for the field.